Impacts of natural resource exploitation and its implications for the environment, society, and the economy - Vadila Hanin (Bioculture Journal, 2026)
Background: Indonesia is widely recognized as a country with abundant natural resources and high biodiversity, consisting of wide variety of flora and fauna that play an important role in maintaining environmental ecosystems. However, the increasing intensity of natural resource exploitation has exceeded sustainable limits, particularly through practices such as illegal logging and deforestation, which contribute to ecosystem degradation and biodiversity loss. This deforestation is carried out for land clearing that is subsequently used for plantations, mining activities, and the expansion for residential areas. Furthermore, their loss has had negative impacts on conservation efforts and the environmental sustainability of surrounding communities. Methods: This study aims to examine and analyze the impacts of natural resource exploitation on environmental, social, and economic aspects in Indonesia. The method used in this study is a qualitative method through a literature review, utilizing a range of national and international scholarly articles as well as relevant policy documents concerning natural resource exploitation in Indonesia. Findings: The results reveal that intensive exploitation of natural resources produces multidimensional impacts encompassing environmental, social, and economic aspects, which are interconnected within a dynamic system. Based on these three aspects, a cyclical feedback relationship emerges in which environmental degradation contributes to reduced economic performance and worsens social conditions, while economic and social pressures, in turn, encourage more intensive exploitation of natural resources. Therefore, natural resource exploitation should not be understood in a fragmented way, but rather as part of an interconnected and integrated system. Conclusion: Addressing deforestation and exploitation requires shifting from fragmented interventions toward holistic, system-based environmental policy. Novelty/Originality of this article: This study introduces an integrated systems framework that conceptualizes natural resource exploitation in Indonesia not as isolated sectoral damages, but as a dynamic, cyclical feedback system interlinking environmental degradation, economic decline, and social pressure.